Smart and Multifunctional Nanomaterials and Applications for Food Safety - Wu, Long; Tang, Xiaoqian; Yu, Wenbo (MDPI - Multidisciplinary Digital Publishing Institute, 2023)
With the aid of smart and functional nanomaterials, various analytical techniques and their applications have been greatly improved. Based on functional nanomaterials, this Reprint contains innovative studies and comprehensive reviews regarding the design of SERS, fluorescence, bioluminescence, and chromatographic assays and electrochemical techniques for the detection of food contaminants. It includes the pretreatment of food samples, signal amplification mechanisms, detection strategies, method construction process, and other topics.